Lupeol suppresses migration and invasion via p38/MAPK and PI3K/Akt signaling pathways in human osteosarcoma U-2 OS cells. Issue 9 (2nd September 2019) - Hsu, Ming-Jie; Peng, Shu-Fen; Chueh, Fu-Shin; Tsai, Chang-Hai; Tsai, Fuu-Jen; Huang, Chih-Yang; Tang, Chih-Hsin; Yang, Jai-Sing; Hsu, Yuan-Man; Huang, Wen-Wen; Chung, Jing-Gung
ABSTRACT: Lupeol, one of the common components from the fruits and natural foods, has been reported to exert antitumor activities in many human cancer cell lines; however, its effects on osteosarcoma cell metastasis were not elucidated. In the present study, lupeol at 10–25 μM induced cell morphological changes and decreased total viable cell number in U-2 OS cells. Lupeol (5–15 μM) suppressed cell mobility, migration, and invasion by wound healing and transwell chamber assays, respectively. Lupeol inhibited the activities of MMP-2 and −9 in U-2 OS cells by gelatin zymography assay. Lupeol significantly decreased PI3K, pAKT, β-catenin, and increased GSK3β. Furthermore, lupeol decreased the expressions of Ras, p-Raf-1, p-p38, and β-catenin. Lupeol also decreased uPA, MMP-2, MMP-9, and N-cadherin but increased VE-cadherin in U-2 OS cells. Based on these observations, we suggest that lupeol can be used in anti-metastasis of human osteosarcoma cells in the future. Graphical abstract: : The possible signaling pathways for lupeol suppressed cell migration and invasion in U-2 OS cells in vitro